An Analysis of the Flouting Maxim Portrayed in Barbie (2023) Movie - Marta, Adira Amabela; Ajeng, Galuh Dwi; Nurchurifiani, Eva (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
Pragmatics is the study of the meaning of conversations, which occurs based on the context and the situation. This study focuses on analyzing the flouting maxim in the Barbie (2023) movie. The researcher aims to identify the types of flouting maxims in the conversations carried out by the characters in the Barbie (2023) movie, and also to capture the implied meaning of what is conveyed through the flouting maxim. This study uses Grice's grand theory, namely the cooperative principle (1975). This research uses a qualitative descriptive method. Meanwhile, the movie and its transcript are used as data sources. The researcher serves as the main instrument in this research. In collecting data, the researcher watched the movie, identified the dialogues that contained flouting maxims, classified them based on the types of flouting maxims, and analyzed their implicatures based on the context of the conversation. Although many studies have discussed Gricean maxims, limited research has focused on how characters in recent popular movies flout maxims to express hidden meanings. The results of this research show that there are four types of flouting maxims in the movie, with a total of 27 data found. Those are flouting maxim of quantity, it was found 6 times; flouting maxim of quality, it was found 12 times; flouting maxim of relation, it was found 7 times; and flouting maxim of manner, it was found 2 times. Researchers also found the implicature of the flouting maxim used by the characters in the Barbie (2023) movie. These findings are expected to help readers understand how pragmatic strategies can reveal implied messages in fictional conversations